DESCRIPTION OF P53 GENE EXPRESSION AND TESTICULAR WEIGHT OF MALE MICE (Mus musculus) FEEDING HUTAN BULO HONEY AND CIGARETTE SMOKE EXPOSURE - Sukoco, Hendro; Irfan, Muhammad; Siswanto, Ferbian Milas (Universitas Syiah Kuala, 2023)
The aim of this study was to determine the expression of the P53 gene and testicular weight of male mice (Mus musculus) given Bulo forest honey and exposed to cigarette smoke. The experimental animals used in this study were 24 male mice which were divided into 4 treatment groups, each group consisting of 6 mice. Mice in group P0 were considered as control group (without treatment), while mice in group 1 (P1) were exposed to 2 cigarettes smoke, while mice in groups 2 (P2) and 3 (P3) were exposed to 2 cigarettes smoke and given Bulo forest honey at a dose of 0.8 ml/day and 0.4 mL/day, respectively. The data obtained were analyzed using one way ANOVA followed by using the Least Significant Difference (LSD) test. The results showed that Bulo forest honey administration did not statistically affect (P0.05) the ratio of testicular weight and P53 gene expression in male mice (Mus musculus) exposed to cigarette smoke for 30 days. It is concluded that the administration of Bulo forest honey at dose of 0.8 mL and 0.4 mL has not been able to increase the testicular weight ratio and reduce the expression of the P53 gene in male mice.